Evaluation of Oil-Water Relative Permeability Curves at A Contaminated Reservoir Condition - Bozdag ., Saziye (Asian Journal of Chemistry, 2010)
A leaking oil pipeline in the Karaduvar district of the city of Mersin has caused contamination of valuable groundwater supplies. Quantities of oil have been release into the groundwater reservoir (aquifer), limiting the value of irrigation well fields. The groundwater in 0.2 km2 (roughly 50 acres) of land is polluted. To solve the problem, first, local geology and hydrogeology of the area were evaluated and GC analysis was made. After the original identification of the problem, existing wells have been monitered and new observation holes have been excavated to further define the problem and several tests have been made. From the results of this work, the source of the pollutants was determined, the leakage was stopped, approximately 500,000 L of oil have been removed and additional contamination of the area was prevented.